Clima laboral en el área administrativa de la Compañía Lexkingsa S.A del cantón Puebloviejo - Manzaba Carranza, Gabriel Leonardo (2020)
This case study describes the working environment of the company Lexkingsa S.A. and how it is used for the purpose of determining the internal employment relationship of the administrative area, so that staff can be involved in meeting the organization's objectives. This research analyzes how the different variables influence an excellent work environment such as: communication, motivation, teamwork, work relationship, training, leadership, among others, positively influencing employees in the administrative area, who demonstrate a firm commitment to the company when carrying out their daily work tasks. It also demonstrates how staff in the administrative area feel empowered in their work areas, indicating that the organization does an excellent job of keeping staff motivated, not only financially but also through the recognition and importance given to them in decision making, creating a healthy and dynamic work environment, and a staff committed to what they do for the organization.